An adaptive localization method of simultaneous two acoustic emission sources based on energy filtering algorithm for coupled array signal. (1st June 2021) - Tai, Junfei; Liu, Xiandong; Wang, Xiaoran; Shan, Yingchun; He, Tian
Highlights: The mechanism of the frequency-domain notch-weighted AE beamforming is derived. The localization procedure of the simultaneous two AE sources is proposed. The simultaneous two AE sources with different energy could be effectively localized. The performance of the method was successfully tested by simulation and experiment. Abstract: This paper proposes a novel localization method of simultaneous two acoustic emission (AE) sources to decouple the two coupled AE waves in the structure and obtain more accurate localization results by means of frequency-domain notch-weighted beamforming. Firstly, the notch-wave theory is analyzed and combined with propagation characteristics of AE waves to derive the mechanism and method of the frequency-domain notch-weighted beamforming. After that, the localization process of the simultaneous two AE sources is proposed based on the presented frequency-domain notch-weighted beamforming method. Then, the simulation is performed to obtain the data of two AE sources emitted in different positions with different energies to study the localizing effect of the frequency-domain notch-weighted beamforming method. Finally, the proposed method is verified by pencil-lead-breaking (PLB) test on a steel plate. The research results show that the frequency-domain notch-weighted beamforming method can effectively localize the simultaneous two AE sources.